Special sensitivity?: the white-collar offender in prison - Stadler, William Andrew (Criminal justice: recent scholarship, 2012)
The white-collar crime problem -- Understanding white-collar crime -- Exploring the special sensitivity hypothesis -- The white-collar inmate experience -- Questioning the special sensitivity hypothesis -- The future of white-collar offender sentencing -- Bibliography -- Index